Comparação do exercício intervalado de alta intensidade com exercício moderado na atenção concentrada de adultos jovens - PINHEIRO, Lurdilene dos Santos (2023)
Introduction: concentrated attention is characterized by the ability of human beings to remain focused in accordance with their objective even with all the stimuli in the environment. One way to increase focused attention is with physical exercise. However, exercise intensity is seen as an important parameter that can modulate the induced effects on attention. Purpose: to investigate and compare the effect of a session of high-intensity interval exercise (HIIT) with moderate exercise (ME) on the focused attention of young adults. Materials and methods: 17 physically active young adults (28.6 ± 4.84 years, 68.8 ± 9.23 kg, 164.2 ± 8.90 cm, 27,0 ± 2,8 kg/m2 ) (44.87 ± 5.90 mL/kg/min). The participants were initially submitted to a familiarization situation, and three experimental situations: control situation (CON), EM and HIIT (performed in random order) to measure the concentrated attention before and after each intervention. On the first visit, measurements of anthropometric variables, determination of maximum oxygen consumption and familiarization with the experimental situation were performed. On the second, third and fourth visit, the participants performed the experimental situations (CON, EM or HIIT) with an interval of 7 days between each situation. In the experimental situations, concentrated attention was evaluated before and after each experimental situation using the Toulouse-Piéron concentrated attention test. In addition, motivation was checked before each situation for experimental control. Statistical analysis: The normality of data distribution (Shapiro Wilk) and homoscedasticity (Levene) were verified. After confirming the normal distribution of variables, two-way Anova with repeated measures and post hoc Bonferroni t-test were used when necessary. The motivation factor was also analyzed using the Friedman test. All results of parametric variables were presented as mean ± standard deviation, non- parametric variables are presented as median and interquartile range (Q1 – Q3) and we adopted a significance level of p<0.05. Results: In the speed variable, there was a significant difference between pre-HIIT (166.4 ± 42.1 points (pts)) and post-HIIT (185.2 ± 38.7 pts), with an improvement of 11.30%. There was also a difference between post HIIT and post CON (185.2 ± 38.7 vs.164.6 ± 37.4 pts, p<0.05), however, there was no significant difference between post HIIT and post EM situations (185.2 ± 38.7 vs. 181.4 ± 42.9 pts, p>0.05). In the EM situation, there was a difference between pre and post-exercise moments (161.3 ± 42.1 vs.181.4 ± 42.9 pts), with an increase of 12.3%. Regarding the quality variable, the post hoc analysis showed differences between pre-HIIT (64.8 ± 41.4 pts) and post-HIIT (45.9 ± 38.2 pts) moments, with an improvement of 29.2%. In addition, there was a significant difference between post HIIT and post CON (45.9 ± 38.2 vs. 66.3 ± 37.1 pts), but there was no significant difference between post HIIT and post EM situations (45.9 ± 38.2 vs 49.4 ± 42.7 pts, p>0.05). In the EM situation, there was a difference between the pre- and post-exercise moments (72.0 ± 38.7 vs. 49.4 ± 42.7 pts), demonstrating a reduction of 31.3%. Conclusion: Both HIIT and EM exercises were able to improve concentrated attention.